Formalization of correlational studies of water problems - Carreon Guillen, Javier; García Lirios, Cruz; Yaneth Quiroz Campas, Celia; Alexander Vallejo Montoya, Elías; Espinoza Morales, Francisco; Hugo Meriño Córdoba, Victor; Ysabel Martínez de Meriño, Carmen; Vicente Ovalles Toledo, Luiz; Judith Brito Carrillo, Clara; Verstapp Bund, Arger (Journal of Model Based Research, 2023)
A methodological note proposes formal structures for correlational studies of water problems. It emphasizes variable definition, confounding control, and reproducibility.
Keywords: Conformity; dependency; conflict and hydrological innovation